P016: Feasibility of a nurse-led smoking cessation intervention in the emergency department. (May 2020) - Tolmie, A.; Erker, R.; Donauer, A.; Sullivan, E.; Graham, T.; Oyedokun, T.; Stempien, J.
Abstract : Introduction: Cigarette smoking is a leading global cause of morbidity and mortality. Multiple studies internationally have established that cigarette smoking prevalence is higher in emergency department (ED) patients than their respective communities. Previously, we demonstrated the smoking prevalence among Saskatoon ED patients (19.6%) is significantly higher than the provincial average (15.1%), and over 50% of smoking patients would be receptive to ED-specific cessation support. The purpose of this project was to identify nurses' beliefs regarding smoking cessation in the ED, and barriers to implementing it in the department. Methods: A questionnaire was administered to all nurses employed at St. Paul's Hospital ED in Saskatoon assessing attitudes towards ED cessations, as well as the benefit and feasibility of three potential interventions: brief cessation counselling, referral to community support programs, and distributing educational resources. The questionnaire included Likert scale numerical ratings, and written responses for thematic analysis. Thematic analysis was performed by creating definitions of identified themes, followed by independent review of the data by researchers. Results: 83% of eligible nurses completed the survey (n = 63). Based on Likert scores, ED nurses rarely attempt to provide cessation support, and would be minimally comfortable with personally providing this service. Barriers identified through thematic analysis included time constraints (68.3%), lack of patient readiness (19%), and lack of resources/follow-up (15.9%). Referral to community support programs was deemed most feasible and likely to be beneficial, while counselling within the ED was believed to be least feasible and beneficial. Overall, 93.3% of nurses indicated time and workload as barriers to providing ED cessation support during the survey. Conclusion: Although the ED is a critical location for providing cessation support, the proposed interventions were viewed as a low priority task outside the scope of the ED. Previous literature has demonstrated that multifaceted ED interventions using counselling, handouts, and referrals are more efficacious than a singular approach. While introduction of a referral program has some merit, having professionals dedicated to ED cessation support would be most effective. At minimum, staff education regarding importance of providing smoking cessation therapy, and simple ways to incorporate smoking cessation counselling into routine nursing care could be beneficial.